Biplane fracture of distal femoral epiphysis: a case report. - W. Wajanavisit (2018)
We report a case of an unusual pattern of fracture in an 11 year-old girl who sustained a distal femoral epiphyseal injury of her right knee after a motorcycle accident. It is a combination of type I and type III epiphyseal injury. This is the so-called biplane fracture of distal femoral epiphysis. The pathomechanism of the injury is a combined adduction and hyperextension type. Open reduction and internal fixation are used in order to achieve anatomic reduction. Three months after operation the fracture was healed with good functional result.